2020
DOI: 10.1109/tci.2020.3039564
|View full text |Cite
|
Sign up to set email alerts
|

Towards Reducing Severe Defocus Spread Effects for Multi-Focus Image Fusion via an Optimization Based Strategy

Abstract: Multi-focus image fusion (MFF) is a popular technique to generate an all-in-focus image, where all objects in the scene are sharp. However, existing methods pay little attention to defocus spread effects of the real-world multi-focus images. Consequently, most of the methods perform badly in the areas near focus map boundaries. According to the idea that each local region in the fused image should be similar to the sharpest one among source images, this paper presents an optimization-based approach to reduce d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…For an unbiased evaluation of the fusion results, visual and objective evaluations were both adopted to compare our method with the other four representative fusion methods, which are the IFCNN, 21 MFF, 15 CNN 22 and RBI, 7 and their specific information is shown in Table 2. Six objective representative evaluation metrics were selected in this section, namely SD (calculated by Equations ( 6) and ( 7)), SSIM (obtained by Equations ( 8) and ( 9)), SF (obtained by Equation ( 11)), PSNR (calculated by Equations ( 13) and ( 14)), Q abf (obtained by Equations ( 15) and ( 16)) and AG (displayed in Equation ( 17)).…”
Section: Resultsmentioning
confidence: 99%
“…For an unbiased evaluation of the fusion results, visual and objective evaluations were both adopted to compare our method with the other four representative fusion methods, which are the IFCNN, 21 MFF, 15 CNN 22 and RBI, 7 and their specific information is shown in Table 2. Six objective representative evaluation metrics were selected in this section, namely SD (calculated by Equations ( 6) and ( 7)), SSIM (obtained by Equations ( 8) and ( 9)), SF (obtained by Equation ( 11)), PSNR (calculated by Equations ( 13) and ( 14)), Q abf (obtained by Equations ( 15) and ( 16)) and AG (displayed in Equation ( 17)).…”
Section: Resultsmentioning
confidence: 99%
“… Ensemble of CNN for multi-focus image fusion [ 6 ] (ECNN). Towards reducing severe defocus spread effects for multi-focus image fusion via an optimization based strategy [ 5 ] (MFF-SSIM). MFF-GAN: An unsupervised generative adversarial network with adaptive and gradient joint constraints for multi-focus image fusion [ 4 ] (MFF-GAN).…”
Section: Methodsmentioning
confidence: 99%
“…Towards reducing severe defocus spread effects for multi-focus image fusion via an optimization based strategy [ 5 ] (MFF-SSIM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Defocus blurring is inevitable when the scene regions (with wider depth range) are out-of-focus due to the limitation of the hardware, i.e., cameras with a finite-size aperture can only focus on the shadow depth of field (DoF) at a time, and the rest scene regions will contain blur [1]. Removing this blur and recovering defocused image details are challenging due to the spatially-varying point spread functions (PSFs) [2], [3], [4]. Recently, some studies address this problem by dual-pixel (DP) sensors found on most modern cameras [5].…”
Section: Introductionmentioning
confidence: 99%